A STUDY ON KNOWLEDGE OF PRACTICING MIDWIVES IN BASRAH ABOUT THEIR TASKS IN REPRODUCTIVE HEALTH CARE - ALABRAHIM Maisaa; ALRamdhan Jinan; Al Abboodi Huda (Scholar Express Journals, 2022)
Introduction: The midwife is a responsible and reliable person who provides care and advice to the mother during pregnancy, childbirth and postpartum period.Objective: The objective of this study was to assess the Knowledge of practicing midwives in Basrah about their tasks and duties in reproductive health care before delivery, during delivery and after birth.Methodology: The study was cross-sectional, with in-depth interviews and questionnaires prepared by the researchers for the study's purposes.Result: This research included a total of 57 midwives: 37 (64.9%) Graduated midwifery obstetric academy and 20(35.1%) Graduated nursery school who is classified with midwifery course,16(28.1%) in the age group (41 -50) , 23(40.4%) of them have more than 11 years of work experience ,50(87.7%) work with a team of two or more , 15(26.3%)of them have no children and42 (73.6%) have from one to seven children. Conclusion: The study show evidence of ineffective practices during labour and delivery among healthcare workers. the results show more than two thirds have good knowledge about immediate postpartum care.
Keywords: A midwife; duties and tasks; antenatal care; postpartum care